Surface Flow and Strain of the Ice Sheet Measured by a Triangulation Chain in Mizuho Plateau - Naruse, R. (1978)
P(論文) Surveys of a triangulation chain extending 250km along the parallel of 72°S in Mizuho Plateau, East Antarctica, were carried out in 1969 and 1973-1974. Obtained from them were horizontal and vertical components of surface velocities of the ice sheet at 141 stations and also principal strains, maximum shear strains, dilatations, and rotations of the surface ice in 140 triangles of the chain. Horizontal velocities of the ice sheet showed small values in the vicinity of the Yamato Mountains, and maximum values of more than 20m/year in a region between 39°E and 40°E. Direction of the flow vector was approximately identical with that of the large-scale maximum slope of the ice surface, but the direction and magnitude of the principal strain showed influence by small-scale surface undulations. In general, the direction of the maximum extension of strain was rather close to that of the ice flow. Tensile strains were more common than compressive strains almost all over Mizuho Plateau. The vertical component of ice velocity was directed downward, which is characteristic of the submergence flow, in the region from 39°E eastward. The amount of snow accumulation was not enough to compensate the deficit of ice mass caused by the submergence flow along the triangulation chain. The mass budget was negative in the zone of 2400-2600m in elevation in the Shirase drainage. departmental bulletin paper